2017
DOI: 10.5664/jcsm.6482
|View full text |Cite
|
Sign up to set email alerts
|

F-Wave Duration as a Specific and Sensitive Tool for the Diagnosis of Restless Legs Syndrome/Willis-Ekbom Disease

Abstract: Study Objectives: Restless legs syndrome, also known as Willis-Ekbom disease (RLS/WED), is a frequent condition, though its pathophysiology is not completely understood. The diagnosis of RLS/WED relies on clinical criteria, and the only instrumental tool, the suggested immobilization test, may lead to equivocal results. Recently, neurophysiological parameters related to F-wave duration have been proposed as a diagnostic aid. The aim of this study is to assess and compare the diagnostic values of these paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Oz O et al, [12] found that while the CSP latency was longer, the CSP duration was shorter in RLS patients compared to controls. While similar findings were reported by Isak B et al, [11] a recent study by Congui P et al, [10] did not find any significant abnormality in CSP in RLS patients probably due to the small sample size or minor differences in the methodology. Han JK et al, [15] investigated the patho-physiological relationship between RLS and small fiber neuropathy using the CSP and found that while the CSP latencies did not differ between RLS patients and healthy controls, the mean CSP duration was significantly longer in RLS patients than in controls.…”
Section: Original Research Articlesupporting
confidence: 83%
See 1 more Smart Citation
“…Oz O et al, [12] found that while the CSP latency was longer, the CSP duration was shorter in RLS patients compared to controls. While similar findings were reported by Isak B et al, [11] a recent study by Congui P et al, [10] did not find any significant abnormality in CSP in RLS patients probably due to the small sample size or minor differences in the methodology. Han JK et al, [15] investigated the patho-physiological relationship between RLS and small fiber neuropathy using the CSP and found that while the CSP latencies did not differ between RLS patients and healthy controls, the mean CSP duration was significantly longer in RLS patients than in controls.…”
Section: Original Research Articlesupporting
confidence: 83%
“…It is therefore imperative that RLS which is a common under-diagnosed condition in India be recognized at an early stage of its inception and prompt treatment be started to improve the patient's 'quality of life'. The diagnosis of RLS primarily depends on the clinical criteria and the only instrumental tool, the suggested immobilization test leads to equivocal results [10]. Some authors have suggested the use of F-wave duration and its ratio with the corresponding muscle action potential as a possible supportive diagnostic tool for RLS patients: both of these were significantly longer when compared to controls [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…(). With central sensitization there would be hyperexcitability (Woolf, ), as seen with alterations in reflex responses shown in previous studies (Bara‐Jimenez et al ., ; Congiu et al ., ; Gunduz et al ., ; Isak et al ., ) as well as in the current study, and hyperalgesia (Woolf, ), which has also been shown in patients with RLS (Bachmann et al ., ; Cho et al ., ; Edwards et al ., ; Stiasny‐Kolster et al ., , ).…”
Section: Discussionmentioning
confidence: 97%
“…CuSPs were studied in various movement disorders. CuSP was abnormal in essential tremor, multiple system atrophy, and Parkinson's disease 10,11 . It was normalized after administration of low-dose propranolol in essential tremor 12 .…”
Section: Discussionmentioning
confidence: 97%